Contrastive Linguistics and Translation Studies. Wlaimir Kaminer's Ausgerechnet Deutschland. Some Proposal of Translation - Ferron, Isabella (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
The present paper aims to investigate the reciprocal relation between contrastive linguistics and the translation studies referring to the language pair German-Italian through the analysis of Wladimir Kaminer’s book Ausgerechnet Deutschland. Geschichten unserer neuen Nachbarn (2018). The book hasn’t been translated in Italian yet, so some text passages will be analyzed, that could make considerable linguistic problems because of their strong cultural character. Kaminer deals in his book with up-to-the-minute topics such as the refugee crisis (2015/16), therefore he depicts interesting linguistic aspects. The vocabulary is especially interesting, as it has particular cultural features, that point out the German culture and way of thinking referring to the global refugee crisis. The lexical features show in the relation between contrastive linguistics and the translation studies the different methods of conceptualizing in a particular culture or more the one throughout the own language. In relation to this, the paper gives a semantic analysis of chosen text passages und tries to find an answer to the following questions: 1) Which effects of the contrastive linguistic are useful for functional aligned translation studies?; 2) How can cultural body of knowledge be integrated in the translating progress?